GEOMAGNETIC OBSERVATIONS IN THE ARCTIC OCEAN. DRIFT STATION ARLIS II, JUNE 3 TO AUGUST 21, 1962 - Walker, James C. G. (1964)
A nuclear resonance magnetometer was operated on Drift Station Arlis II in the Arctic Ocean during the summer of 1962. The measurements cover the period June 3 to August 21, 1962. During this period Arlis II drifted over a region bounded by latitudes 81 degrees 30 minutes and 82 degrees 20 minutes North, and by longitudes 161 and 169 degrees East, corresponding to a geomagnetic latitude of approximately 72 degrees North. The drift track is shown. At the time of the magnetic measurements, Arlis II was in water about 2800 meters deep over the Wrangel Abyssal Plain. A strip chart record of the total intensity of the magnetic field was made at a speed of 4 minutes to the inch and a sensitivity of approximately 11 gamma to the inch. Instantaneous hourly values read from this record are tabulated. The hourly values are plotted against Greenwich Mean Time. Daily averages of the magnetic field total intensity measured on Arlis II are compared with similar data obtained on Fletcher's Ice Island (T-3) in 1961. (Author)